Fracture-related infection: A consensus on definition from an international expert group. Issue 3 (March 2018) - Metsemakers, WJ.; Morgenstern, M.; McNally, M.A.; Moriarty, T.F.; McFadyen, I.; Scarborough, M.; Athanasou, N.A.; Ochsner, P.E.; Kuehl, R.; Raschke, M.; Borens, O.; Xie, Z.; et al.
Abstract: Fracture-related infection (FRI) is a common and serious complication in trauma surgery. Accurately estimating the impact of this complication has been hampered by the lack of a clear definition. The absence of a working definition of FRI renders existing studies difficult to evaluate or compare. In order to address this issue, an expert group comprised of a number of scientific and medical organizations has been convened, with the support of the AO Foundation, in order to develop a consensus definition. The process that led to this proposed definition started with a systematic literature review, which revealed that the majority of randomized controlled trials in fracture care do not use a standardized definition of FRI. In response to this conclusion, an international survey on the need for and key components of a definition of FRI was distributed amongst all registered AOTrauma users. Approximately 90% of the more than 2000 surgeons who responded suggested that a definition of FRI is required. As a final step, a consensus meeting was held with an expert panel. The outcome of this process led to a consensus definition of FRI. Two levels of certainty around diagnostic features were defined. Criteria could be confirmatory (infection definitely present) or suggestive. Four confirmatory criteria were defined: Fistula, sinus or wound breakdown; Purulent drainage from the wound or presence of pus during surgery; Phenotypically indistinguishable pathogens identified by culture from at least two separate deep tissue/implant specimens; Presence of microorganisms in deep tissue taken during an operative intervention, as confirmed by histopathological examination. Furthermore, a list of suggestive criteria was defined. These require further investigations in order to look for confirmatory criteria. In the current paper, an overview is provided of the proposed definition and a rationale for each component and decision. The intention of establishing this definition of FRI was to offer clinicians the opportunity to standardize clinical reports and improve the quality of published literature. It is important to note that the proposed definition was not designed to guide treatment of FRI and should be validated by prospective data collection in the future.